Demystifying dementia: what generalists need to know - Shyh Poh-Teo (Medicina Universitaria)
Dementia is a group of diseases affecting thinking, memory, reasoning, personality, mood, and behavior. It is a progressive condition, with gradual worsening in brain function affecting a person’s ability to carry out activities of daily living. When the Alzheimer’s Society of Maldives held public awareness sessions on dementia, it was found that there were frequently asked questions raised during panel discussions were similar across different venues. This review aims to demystify dementia and covers what generalists need to know about dementia as clinicians and to raise awareness regarding dementia among the community. The global dementia burden and the impact of dementia are outlined. The common types, symptoms, and stages of dementia, diagnosis, treatment, support, and genetic and modifiable risk factors are described.